Determination of Decisions to Use E-Money Applications (QRIS) - Priyombodo, Bony; Nurchayati, Nurchayati; Sulistyani, Sulistyani; Widayati, Tri (Research Horizon, 2024)
In the era of digital industrial growth and industrial revolution 4.0, the banking sector is experiencing significant changes. This research aims to analyze the factors that influence the decision to use the e-money application (QRIS) by Bank Rakyat Indonesia KC Semarang Pandanaran customers. The factors considered are e-service quality, user experience, and usefulness. The population in this study were customers of Bank Rakyat Indonesia KC Semarang Pandanaran, with the sample size used in this study being 100 customers taken using a purposive sampling technique, with criteria customers who have used QRIS at least 2 times. The data source used is primary data, with data collection methods using questionnaires. The data analysis technique used in this research is multiple linear regression analysis. The research results show that partially, e-service quality, user experience, and usability have a positive and significant influence on usage decisions. customers. The significance results obtained indicate that the higher the e-service quality, the better the user experience, and the higher the usefulness, the decision to use customers will increase. The implication of these findings is the importance of paying attention to and improving these factors in an effort to improve usage decisions customers in using the e-money application (QRIS).